Current trends in amorphous magnetism - COEY, JOHN MICHAEL DAVID (IEEE, 1984)
Recent research on some topics in amorphous magnetism is reviewed and questions are posed which should be answered by future work. The topics are i) appearance of magnetism in binary alloys of the 3d transition elements Fe, Co and Ni with sp elements, ii) conflicting ground states of amorphous iron (ferromagnetic, asperomagnetic, paramagnetic), inferred by extrapolating different Fe//xM//1//0//0// minus //x system to x equals 100, iii) influence of hydrogen on the magnetic properties of metallic glasses, iv) random magnetic anisotropy and v) amorphous ionic compounds with purely antiferromagnetic interactions.
PUBLISHED
Keywords: Physics